Role of tranexamic acid via intravenous and irrigation fluid route in controlling TURP-associated bleeding - Vinay S. Kundargi; Santosh Patil; Siddanagouda B. Patil; Manoj K. Vaidya; Basavesh S. Patil; A. Nawaz Shariff; Vikas Shukla (African Journal of Urology)
Abstract Background This study aims to evaluate the efficacy and safety of tranexamic acid (TXA) administered via the I/V (Intravenous) route and irrigation fluid route during TURP to directly target the bleeding site. Methods A total of 105 cases undergoing bipolar–TURP with gland size 40–100 g were randomized into three groups—control/placebo group (n = 35), I/V group (n = 35) (received 1gm TXA 20 min before the procedure) and irrigation group (n = 35) (received 500 mg TXA in every 3000 ml irrigation fluid up to a maximum of 2 g). Blood loss was estimated by recording haemoglobin and hematocrit at 4 h after the procedure and on first postoperative day. Other parameters such as resection time, intraoperative endoscopic vision, irrigation fluid volume and complications were noted. Results When measured at 4 h postoperatively, the drop in haemoglobin and haematocrit, respectively, was maximum in the control group (ΔHb = 0.78 g/dl, ΔHCT = 1.23%) followed by the irrigation group (ΔHb = 0.51 g/dl, ΔHCT = 0.72%) and was least in the I/V group (0.27 g/dl, 0.62%). The intergroup analysis showed significant difference only between the control vs I/V group (ΔHb p = 0.0163, ΔHCT p = 0.0253). On postoperative day 1, the drop in haemoglobin and haematocrit, respectively, was maximum in the control group (1.10 g/dl, 1.63%) followed by the irrigation group (0.828 g/dl, 0.911%) and was least in the I/V group (0.811 g/dl, 0.948%). The intergroup analysis showed significant difference between the control vs irrigation group (ΔHb p = 0.026, ΔHCT p = 0.0001) and control vs I/V group (ΔHb p = 0.016, ΔHCT p = 0.0003). Total resection time, average volume of irrigation fluid and average postoperative stay were comparable. No significant complications were observed. Conclusions TXA, given either via I/V or irrigation fluid route, reduces postoperative blood loss associated with TURP. Both routes are superior to placebo, but neither is superior to the other. TXA via the intravenous route also reduces intraoperative blood loss, but the same advantage is not observed with administration through irrigation fluid. TXA via either route has no impact on endoscopic vision. Both routes of administration are safe with no reported side effects.